Long term effect of selective muscle strengthening in athletes with patellofemoral pain syndrome - Ramazzina, Ileana; Pogliacomi, Francesco; Bertuletti, Silvia; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: The purpose of the study was to examine the long term effects of a selective muscle strengthening program in reducing pain and improving knee function and strength in athletes with Patellofemoral Pain Syndrome. Methods: A total of one hundred and thirty four athletes were enrolled in the study. All patients were evaluated with Isokinetic Test, Cincinnati Knee Rating System and Visual Analogue Scale. The selective muscle strengthening consisted of 8 weeks of exercises performed 3 times in the first 4 weeks and twice in the last 4 weeks. The muscle strengthening program was performed between 30-90° of knee flexion. During the first 4-weeks treatment we used closed kinetic chain exercises with 3 sets of 8 repetitions at 80% of maximum load. In the last 4-weeks we added open kinetic chain exercises at 70% of maximum load with 3 sets and 10 repetitions to improve the resistance. Results: Analyzing data at the beginning and at the end of the treatment for Isokinetic test, Cincinnati and Visual Analogue Scale we observed a significant scores improvement. At 1 year follow-up the clinical improvements were maintained and everyone followed the recommended program because did not perform the maintenance program. At 2 years follow-up no athletes presented relapses; only four patients were excluded from program. Conclusions: We believe that our program of selective muscle strengthening should resolve pain and improve knee function and strength as results in obtained scores and could be critical to avoid painful relapses.